THE EXPRESSION OF IDEAS OF NATIONAL PRIDE AND PATRIOTISM IN THE WORKS OF ZULFIYA - Toshpulatova, D.B.; Saydullayeva, S.M. (SCIENCE and SOCIETY, 2026)
In this article, the ideas of national pride and patriotism were artistically and aesthetically expressed in the work of Zulfiya, knowing the inextricable connection of these national ideas with the concept of spiritual perfection and the philosophical knowledge that flourished in his world enriched the mood with a deep look at the world, carried out an analysis on a scientific basis and reflected in the main place in the literary process.
Keywords: national pride and patriotism; loneliness; Zulfia's life; creative analysis; description; deep thinking; ideological - aesthetic view